Imperialne interpretacje rewolucji przemysłowej w Anglii - Machaj, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article briefly addresses some of the mistaken interpretations of the Industrial Revolution. In each session the following themes are shortly related to the industrial revolution: aristocracy, slavery, banking system and limited liability, public debt, navigation acts, foreign trade and colonies, and public debt. Last section points to the essence of the industrial revolution, which boils down to innovation implementations, beneficial to the massive consumers
Keywords: rewolucja przemysłowa; interwencjonizm; wzrost gospodarczy